Ð Ð¾Ð»ÑŒ Ð¿ÐµÑ€ÐµÐ¾Ñ…Ð»Ð°Ð¶Ð´ÐµÐ½Ð¸Ñ Ð² ÑÐ¾Ñ…Ñ€Ð°Ð½ÐµÐ½Ð¸Ð¸ ÐºÐ»Ð¾Ð½Ð¾Ð³ÐµÐ½Ð½Ñ‹Ñ… ÑÐ²Ð¾Ð¹ÑÑ‚Ð² Ñ„Ð¸Ð±Ñ€Ð¾Ð±Ð»Ð°ÑÑ‚Ð¾Ð¿Ð¾Ð´Ð¾Ð±Ð½Ñ‹Ñ… ÐºÐ»ÐµÑ‚Ð¾Ðº-Ð¿Ñ€ÐµÐ´ÑˆÐµÑÑ‚Ð²ÐµÐ½Ð½Ð¸ÐºÐ¾Ð² ÑÐ¼Ð±Ñ€Ð¸Ð¾Ð½Ð°Ð»ÑŒÐ½Ð¾Ð¹ Ð¿ÐµÑ‡ÐµÐ½Ð¸ Ñ‡ÐµÐ»Ð¾Ð²ÐµÐºÐ° Ð¿Ð¾ÑÐ»Ðµ ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ñ - Skorobogatova, N. G.; Grischuk, V. P.; Petrenko, A. Yu. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2006)
Effect of different freezing conditions on human fetal liver (HFL) cell viability and colony-forming activity of HFL fibroblast-like progenitor cells (FPCs) was investigated. This progenitor type was established to be a high sensitive to a damaging effect of overcooling. Overcooling reduction at a slow three-step freezing enables a successful cryopreservation of FPCs in primary suspension of HFL cells with preservation of their clonogenic properties.